Analisis Kesesuaian Indikator terhadap Kompetensi Dasar pada Pelajaran Matematika oleh Guru Sekolah Menengah Palembang - Indaryanti Indaryanti; Ely Susanti; Nyimas Aisyah; Scristia Scristia (Universitas Maritim Raja Ali Haji, 2019)
This research aims to describe competence level and competence hierarchy on indicators developed by 23 middle schools teacher from South Sumatera Province, using indicator and objectives references to Revised Bloom’s Taxonomy and National Standard of Education. The result suggest that the competence levels are overlapping at the indicators and the developed indicators are limited to minimal competence of learning standards.